ANALISIS TOKOH UTAMA DAN NILAI PENDIDIKAN KARAKTER DALAM NOVEL PADA SEBUAH KAPAL KARYA N.H. DINI SERTA RELEVANSINYA SEBAGAI BAHAN AJAR DI SMA - Chriszia, Deyana; Suyitno, Suyitno; Suryanto, Edy (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This research intends to describe and explain: (1) Intrinsic elements of the novel of Pada Sebuah Kapal by N. H. Dini; (2) The character building elements of the main role of the novel of Pada Sebuah Kapal by N. H. Dini; (3) The character education values in the novel of Pada Sebuah Kapal by N. H. Dini; and (4) The result of the study of the novel of Pada Sebuah Kapal by N. H. Dini for teaching literature of XII Grade of senior high school students based on Basic Competencies 3.9, that is the analysis of context and linguistic of the novel. This research is descriptive qualitative research with the psychology literature study. The sample was collected by purposive sampling method. The data were collected by interview and document analysis. The data validity test that was used is the triangulation of data sources and member check or informant review. The data was analysed by flows analysis models method. The research results are: (1) Intrinsic elements that consist of theme, character and characterization, setting, plot, and point of view is interconnected and build each other in the process of the creation of literature. Through the analysis of intrinsic elements of the novel, the reader will be easier to understand the context of the read novel; (2) The character building elements of Sri as the main role consists of id, ego, and superego. Ego element is the dominant element because it affects the most of the decision making for the main role lives; (3) The character education values in the novel of Pada Sebuah Kapal by N. H. Dini consist of discipline, work hard, curiosity, nationality spirit, appreciating achievement, friendly/communicative, love to read, and responsibility. The responsibility value is the dominant value because it appears the most in the entire novel and able to affect other character education values; (4) The novel of Pada Sebuah Kapal by N. H. Dini can be used for teaching literature of XII Grade of senior high school students based on Basic Competencies 3.9, that is the analysis of context and linguistic of the novel. This novel also contains the character education values that able to strengthen students’ character that able to be a consideration in determining the good or bad values in daily life.